2003
DOI: 10.1002/ana.10553
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage induces macrophage activation and matrix metalloproteinases

Abstract: Intracerebral hemorrhage (ICH) is characterized by parenchymal hematoma formation with surrounding inflammation. Matrix metalloproteinases (MMPs) have been implicated in the pathogenesis of neurological diseases defined by inflammation and cell death. To investigate the expression profile and pathogenic aspects of MMPs in ICH, we examined MMP expression in vivo using a collagenase-induced rat model of ICH. ICH increased brain MMP-2, -3, -7, and -9 mRNA levels relative to sham-injected (control) animals in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
271
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 330 publications
(287 citation statements)
references
References 52 publications
16
271
0
Order By: Relevance
“…Moreover, we analyzed CM352's effect on MMPs that had been reported to be upregulated after ICH in humans and experimental models 14, 25. We previously reported that CM352 efficiently inhibited MMP‐3 and MMP‐10,20 and in this study we describe that it also inhibits MMP‐2, MMP‐9, and MMP‐12 in the nanomolar range.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, we analyzed CM352's effect on MMPs that had been reported to be upregulated after ICH in humans and experimental models 14, 25. We previously reported that CM352 efficiently inhibited MMP‐3 and MMP‐10,20 and in this study we describe that it also inhibits MMP‐2, MMP‐9, and MMP‐12 in the nanomolar range.…”
Section: Resultsmentioning
confidence: 68%
“…Rapid MMP upregulation after ICH has been proposed to cause neurovascular matrix degradation, proteolyzing the basal lamina around blood vessels and disrupting endothelial tight junctions, leading to edema, hemorrhage, and cell death 13. Based on this rationale, early treatment with broad‐range MMP inhibitors has been used in experimental models to reduce brain damage after ICH 13, 14…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Rosenberg and Navratil (1997) first demonstrated that MMP2 and 9 activation increased 16 to 24 h after collagenase-induced ICH in rats. Extending this work, a study by Power et al (2003) indicated that collagenase-induced hemorrhage in rat increased brain MMP2, 3, 7, and 9 mRNA levels at 24 h, but MMP12 (macrophage metalloelastase) was the most highly induced ( > 80-fold) at day 7. Immunohistochemistry showed MMP12 to be localized in activated microglia/macrophages surrounding the hematoma.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 68%
“…11,12 Inflammation after ICH can cause disruption of the blood-brain barrier, 13 elicit brain edema, 14 and contribute to cell death after hemorrhage via cytotoxic mediators. 15,16 In this context, we have focused on leptin and inflammation after ICH, and brain edema is used as an important marker of brain injury related to inflammation. We sought to investigate whether leptin has a detrimental effect on ICH in terms of post-ICH inflammation.…”
Section: Introductionmentioning
confidence: 99%